2012
DOI: 10.1097/meg.0b013e328351b2c2
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the symptoms and psychological factors that influence quality of life in patients with irritable bowel syndrome

Abstract: There are significant gender differences in the symptoms, psychological rating, and QOL scores in IBS. Somatic symptoms, anxiety, and depression all contribute to the negative impact of IBS. Our findings suggest that gender differences should be recognized in IBS treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
57
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 34 publications
11
57
3
2
Order By: Relevance
“…This could be in line with some recent evidences demonstrating more severe IBS symptoms as well as negative impacts on patients' quality of life in cases with other neurologic and/or psychologic co-morbidities such as anxiety and depression 23,24. All of these findings are supporting the neurologic-related identity of IBS and more specifically the association between RLS and symptom severity in IBS patients, which could be linked to serotonin transmission shown to be involved in both conditions of IBS25 and RLS 26…”
Section: Discussionsupporting
confidence: 91%
“…This could be in line with some recent evidences demonstrating more severe IBS symptoms as well as negative impacts on patients' quality of life in cases with other neurologic and/or psychologic co-morbidities such as anxiety and depression 23,24. All of these findings are supporting the neurologic-related identity of IBS and more specifically the association between RLS and symptom severity in IBS patients, which could be linked to serotonin transmission shown to be involved in both conditions of IBS25 and RLS 26…”
Section: Discussionsupporting
confidence: 91%
“…These differences were not due to differences in UCPPS symptom severity or age. Increased co-morbid pain symptoms have also been reported for women with IBS compared to men despite similar IBS severity and level of psychological symptoms [17, 18]. A recent study also found women with UCPPS are more likely to report bothersome non-urologic symptoms across multiple organ systems than men with UCPPS.…”
Section: Discussionmentioning
confidence: 97%
“…24 The IBS-D subtype was also more prevalent in males, which was consistent with other epidemiological studies in Asia. [24][25][26] The highest medical costs in previous European studies were associated with older IBS patients, 24 which might be related to more frequent hospital admission of older patients. However, in the present study, medical costs, resource utilization and claims were highest for middle-aged patients 40-59 years, which is consistent with data from the US.…”
Section: Discussionmentioning
confidence: 99%